PENGARUH MEDIA PROMOSI KESEHATAN BUKU SAKU TERHADAP PENGETAHUAN KESEHATAN REPRODUKSI REMAJA DI MAN 1 KOTA BLITAR - Dea Ayu Wulansari; Sri Winarni; Handy Lala (Poltekkes Kemenkes Malang, 2021)
WHO states that Indonesia is ranked seventh in the world in cases of early marriage, in Blitar City itself there are still many cases of early marriage and premarital sexual adolescents where throughout January 2018 7 teenagers in Blitar City with an average age of 15 to 17 years married. The Blitar City Health Office 2017 said that the number of children who were pregnant was around 73 children with a total of 12 children who had sex before marriage or premarital sex. This indicates that adolescent knowledge about reproductive health itself is still inadequate which can have an impact on adolescent sexual behavior that is deviant. This type of research is quantitative research, with a pre experimental design in the form of One Group Pretest Posttest Design. This research was conducted in April 2021. The population of this research is the students of class 11 IPA 5 at MAN 1 Blitar City with a total of 37 people. Sampling in this study used the total side technique. Data analysis used the Wilcoxon Signed Rank Test. The average value of knowledge before education is 57.70 and the average value of knowledge after education is 84.59. The results showed that there was an influence of pocket book health promotion media on adolescent reproductive health knowledge in MAN 1 Blitar City or p equal 0.000.